Analisis Perlakuan Akuntansi Aset Tetap Berdasarkan PSAP Nomor 07 pada SKPD Dinas Kebudayaan, Kepemudaaan dan Olahraga Serta Pariwisata (Bidang Pariwisata) Kota Tarakan - Olivia Pamilangan Andilolo; Akmal Akmal; Anisah Muharamah Safitri; Deviana Deviana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Activities that have tasks and functions according to their provisions require fixed assets, which are an important component in supporting their operations. Indonesia uses Government Accounting Standard Statement (PSAP) Number 07 on fixed asset accounting as the asset treatment system. Every government agency that reports on its accounting treatment, including recognition, valuation, presentation, and disclosure, must use this standard statement. In addition, as a task support unit for the Tarakan City Tourism Office, the Tourism Office also provides financial reports. The purpose of this study is to determine whether this office has presented financial statements in accordance with PSAP No. 07. This research uses a qualitative descriptive approach with data collection through interviews, observation, and documentation. The results of this study indicate that the asset components of PSAP No. 07, namely asset classification, recognition, measurement, valuation, expenditure, depreciation, termination and disposal, and disclosure have met the principles of PSAP No. 07 on fixed asset accounting.